Exquisite Materials : Episodes in the Queer History of Victorian Style - Joseph, Abigail (Book collections on Project MUSE., 2019)
Exquisite Materials explores the connections between gay subjects, material objects, and the social and aesthetic landscapes in which they circulated. Each of the book's four chapters takes up as a case study a figure or set of figures whose life and work dramatize different aspects of the unique queer relationship to materiality and style. These diverse episodes converge around the contention that paying attention to the multitudinous objects of the Victorian world-and to the social practices surrounding them-reveals the boundaries and influences of queer forms of identity and aesthetic sensibility that emerged in the mid-nineteenth century and have remained recognizable up to our own moment. In the cases that author Abigail Joseph examines, objects become unexpected sites of queer community and desire.